Employees’ knowledge determinants in SMEs: the case of Slovenia - Gomezelj, Doris Omerzel; Antončič, Boštjan (Journal of Business Economics and Management, 2014)
This paper presents various definitions of knowledge as human capital, and analyses some fundamental challenges regarding the measurement of employees’ knowledge of a firm, especially in small and medium enterprises (SMEs). The paper reviews the literature pertaining to the assessment of knowledge assets, proceeds to develop a model of SME employees’ knowledge, and presents the results of an empirical test conducted among 173 Slovenian SMEs. Scales were tested for reliability and validity. A structural equation modelling technique was used to verify the theoretically proposed model of the employees’ knowledge. The multidimensionality of the developed SME knowledge construct was confirmed. The proposed model of the employees’ knowledge consists of five main dimensions: innovation capabilities and willingness to learn, attitude, job qualification, formal education, and work experience. To verify and confirm the proposed model, an exploratory and confirmatory factor analysis was performed. The new construct and concept developed in this study offers a near complete picture that can be used as a research framework in future examinations of the importance of knowledge for SME performance.